2016
DOI: 10.1002/tox.22237
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane‐induced apoptosis in human leukemia HL‐60 cells through extrinsic and intrinsic signal pathways and altering associated genes expression assayed by cDNA microarray

Abstract: Sulforaphane (SFN), one of the isothiocyanates, is a biologically active compound extracted from cruciferous vegetables, and has been shown to induce cytotoxic effects on many human cancer cells including human leukemia cells. However, the exact molecular mechanism and altered gene expression associated with apoptosis is unclear. In this study, we investigated SFN-induced cytotoxic effects and whether or not they went through cell-cycle arrest and induction of apoptosis and further examined molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…Caspases, cysteinyl aspartate-specific proteases, are involved in anticancer drug-induced cancer cell apoptosis, and can be activated during apoptosis in a self-amplifying cascade (49,50). Our results revealed that fisetin significantly increased caspase-3, -8 and -9 expression (Figure 5), showing the involve¬ment of caspases in apoptosis of HSC3 cells.…”
Section: Discussionmentioning
confidence: 68%
“…Caspases, cysteinyl aspartate-specific proteases, are involved in anticancer drug-induced cancer cell apoptosis, and can be activated during apoptosis in a self-amplifying cascade (49,50). Our results revealed that fisetin significantly increased caspase-3, -8 and -9 expression (Figure 5), showing the involve¬ment of caspases in apoptosis of HSC3 cells.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, in human being, sulforaphane displays the multiple interesting biological functions: such as anti-cancer effects (Li et al, 2011;Amin and Shankar, 2015;Dandawate et al, 2016;Leone et al, 2017;Jiang et al, 2018;Sita et al, 2018), antioxidant functions (Negrette-Guzman et al, 2013), anti-Helicobacter pylori activity (Yanaka, 2017), photo aging prevention (Sikdar et al, 2016), prevention of obesity (Martins et al, 2018), and general health benefits (Vanduchova et al, 2019). On the other hand, although numerous reports concerning to the chemopreventive and chemotherapeutic properities of solid tumors are available, there is little information on the properities of sulforaphane in leukemia cells (Choi et al, 2008;Fimognari et al, 2008;Suppipat and Lacorazza, 2014;Fimognari et al, 2014;Shih et al, 2016;Shang et al, 2017;Brown et al, 2017;Koolivand et al, 2018). Unfortunately, the understanding of the effects of sulforaphane on human leukemia cells with mechanisms is incompletely explored till now.…”
Section: Introductionmentioning
confidence: 99%
“…This phytochemical has a strong antioxidant potential and has proven to be an important cancer-preventive candidate, exhibiting high activity that inhibits the proliferation of cancer cells and induces apoptosis in many cancers (Gupta et al 2014;Sestili and Fimognari 2015). Although inhibition of the proliferation of cancer cells by sulforaphane in some cell lines has been reported to be associated with G1 arrest in the cell cycle (Shen et al 2006;Bryant et al 2010;Wang et al 2012), many studies have shown that it induces G2/M arrest associated with apoptosis in multiple cancer types (Singh et al 2004;Matsui et al 2007;Chu et al 2009;Suppipat et al 2012;Wang et al 2015;Byun et al 2016;Shang et al 2017). The effects of sulforaphane on cell cycle progression have also been reported to be specific for mitotic arrest, but not the G2 phase, which is associated with destruction of microtubule polymerization (Jackson and Singletary 2004;Mi et al 2008;Xiao et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of sulforaphane on cell cycle progression have also been reported to be specific for mitotic arrest, but not the G2 phase, which is associated with destruction of microtubule polymerization (Jackson and Singletary 2004;Mi et al 2008;Xiao et al 2012). In addition, it has been shown in various previous studies that ROS act as key regulators in the induction of apoptosis by sulforaphane (Singh et al 2004;Wang et al 2015;Byun et al 2016;Shang et al 2017). Further, recent results from Mondal et al (2016) demonstrate that induction of apoptosis and inhibition of migration of human gastric cancer cells by sulforaphane are associated with increased ROS production and blocking of several intracellular signaling pathways.…”
Section: Introductionmentioning
confidence: 99%